2011
DOI: 10.1007/s13197-011-0520-z
|View full text |Cite
|
Sign up to set email alerts
|

Starch accumulation, activities of key enzyme and gene expression in starch synthesis of wheat endosperm with different starch contents

Abstract: In order to investigate starch accumulation, and the enzymes activity changes and the expression levels of genes and their relationships among them at different developmental stages of wheat grain. We choose Annong9912 and E28 were used in the study. During starch accumulating rate and grain filling rate, and there were obvious genotype difference between Annong9912 and E28. Whether low or high starch content of starch content, the accumulation courses of amylopectin, amylose and total starch were well fitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 48 publications
4
47
0
Order By: Relevance
“…The present study aimed at finding a possible involvement of starch synthases in the determination of different A-type granule sizes. As shown in previous studies, which focused on temporal or spatial patterns of starch synthesis gene expression [30][31][32], the expression of our studied starch biosynthesis genes markedly increased at the early stage of grain filling (from 5 to 10 DPA) and remained at the same level at 15 DPA. Even though it was confirmed that changes in starch synthases (SS and GBSS) activity is closely related to the starch granule size distribution during grain filling [7] no obvious evidence for differences in relative gene expression between genotypes contrasting in A-type granule size was found (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…The present study aimed at finding a possible involvement of starch synthases in the determination of different A-type granule sizes. As shown in previous studies, which focused on temporal or spatial patterns of starch synthesis gene expression [30][31][32], the expression of our studied starch biosynthesis genes markedly increased at the early stage of grain filling (from 5 to 10 DPA) and remained at the same level at 15 DPA. Even though it was confirmed that changes in starch synthases (SS and GBSS) activity is closely related to the starch granule size distribution during grain filling [7] no obvious evidence for differences in relative gene expression between genotypes contrasting in A-type granule size was found (Figure 1).…”
Section: Discussionsupporting
confidence: 75%
“…It cleaves a-1,4 bonds on both amylose and amylopectin molecules and reattaches the released glucan segments to the same or another glucan chain through the formation of a-1,6 linkages (Hurkman et al 2003;Wang et al 2014). There are reports showing that the sucrose-to-starch conversion is catalyzed by multiple isoforms of the enzymes or proteins involved, such as SuSase 2, 3, and 4 (SuS2, SuS3, SuS4), AGPase small subunit 1 and 2 (AGPS1 and AGPS2), AGPase large subunit 1 and 2 (AGPL1 and AGPL2), soluble StSase IIa, b and c (SSSIIa, SSSIIb, and SSSIIc), granule-bound StSase I and II (GBSSI and GBSSII) and SBE I, IIa and IIb (SBEI, SBEIIa, and SBEIIb) (Ishimaru et al 2005;Jeng et al 2007;Wang et al 2008Wang et al , 2014Zhu et al 2011). Each isoform of them may play a distinct role in the process of sucrose-to-starch conversion (Nakamura 2002;Ishimaru et al 2005;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are reports showing that the sucrose-to-starch conversion is catalyzed by multiple isoforms of the enzymes or proteins involved, such as SuSase 2, 3, and 4 (SuS2, SuS3, SuS4), AGPase small subunit 1 and 2 (AGPS1 and AGPS2), AGPase large subunit 1 and 2 (AGPL1 and AGPL2), soluble StSase IIa, b and c (SSSIIa, SSSIIb, and SSSIIc), granule-bound StSase I and II (GBSSI and GBSSII) and SBE I, IIa and IIb (SBEI, SBEIIa, and SBEIIb) (Ishimaru et al 2005;Jeng et al 2007;Wang et al 2008Wang et al , 2014Zhu et al 2011). Each isoform of them may play a distinct role in the process of sucrose-to-starch conversion (Nakamura 2002;Ishimaru et al 2005;Wang et al 2014). Although many studies have been done on the relationship between starch biosynthesis and activities or gene expressions of the enzymes involved (Nakamura 2002;Ishimaru et al 2005;Jeng et al 2007;Zhu et al 2011;Wang et al 2014), little is known about whether and how post-anthesis moderate soil drying enhances grain filling by regulating sink activity, in terms of the activities and gene expressions of the enzymes in sucrose-to-starch conversion in rice spikelets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It evolved from research that showed that glutenin genes control chapatti quality, hence proving that chapatti quality is a genetically controlled character (Anjum et al, 2000;Srivastava et al, 2003). There are also other biochemical components like triticin, starch or lipids in wheat which regulate chapatti quality Ohm and Chung 2002;Singh et al, 1993;Wang et al, 2014). Review of literature reveals that the identification of putative candidate genes specifically for chapatti quality has been done on a smaller set of wheat samples (Anjum et al, 2000;Srivastava et al, 2003;Srivastava et al, 2002).…”
Section: 1) Introductionmentioning
confidence: 99%